An obstetric outcome in pregnant women with consumption of tobacco - Kansara, Vijay; Pateliya, Pinal Ambalal; Karia, Jil; Kadakar, Kunal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Tobacco is known to be an established cause of adverse pregnancy outcome. Scientific studies, encompassing various ethnic groups, cultures and countries, have shown that cigarette smoking during pregnancy significantly affects mother, unborn fetus and the newborn baby. Methods: A hospital based cross sectional study was performed on 933 patients, separated in two groups: tobacco users and tobacco non-users and findings from each group were compared. Results: Incidence of complications like anemia, PIH and abruption increase with maternal usage of tobacco during pregnancy, chances of preterm delivery and ectopic pregnancy was raised, rate of wound complication was more in tobacco user women. There was no significant difference in mode of delivery. Conclusions: In the present study may establish association of tobacco consumption with adverse neonatal and obstetrics outcome and may encourage administration to focus on IEC (information, education, communication) to reduce tobacco consumption during pregnancy. Incidence of complications like anemia, PIH, abruption increase with maternal usage of tobacco during pregnancy. Chances of preterm delivery and ectopic pregnancy, was raised usage with of tobacco.